Comparison of stable environment in prior approved and non-prior approved horse stables - Lundvall, Josefine (SLU/Dept. of Animal Environment and Health (until 231231), 2013)
To establish good horse welfare there are several factors that need to be considered. One important factor is the environment in which the horses are kept. In Sweden horses are stabled during long periods of time in the cold season and consequently the stable environment is even more important. The most essential environmental factors in a horse stable are ambient temperature, relative humidity (RH) and concentrations of contaminants in the stable air. The air in a horse stable contains dust, noxious gases, moulds and microorganisms which all can contribute to developing respiratory diseases in horses. In Sweden it is legislated that when a livestock building is erected, altered or extended it needs a prior approval from the County Administrative Board. The aim with the legislation is to approve the building from an animal welfare and animal health perspective and to prevent welfare issues.